Early Daoist Dietary Practices: Examining Ways to Health and Longevity - Arthur, Shawn (Lexington Books, 2013)
Much as the modern Western world is concerned with diets, health, and anti-aging remedies, many early medieval Chinese Daoists also actively sought to improve their health and increase their longevity through specialized ascetic dietary practices. Focusing on a fifth-century manual of herbal-based, immortality-oriented recipes—the Lingbao Wufuxu (The Preface to the Five Lingbao Talismans of Numinous Treasure)—Shawn Arthur investigates the diets, their ingredients, and their expected range of natural and supernatural benefits. Analyzing the ways that early Daoists systematically synthesized religion, Chinese medicine, and cosmological correlative logic, this study offers new understandings of important Daoist ideas regarding the body’s composition and mutability, health and disease, grain avoidance (bigu) diets, the parasitic Three Worms, interacting with the spirit realm, and immortality. This work also employs a range of cross-disciplinary scientific and medical research to analyze the healing properties of Daoist self-cultivation diets and to consider some natural explanations for better understanding Daoist asceticism and its underlying world view.